Specialist selection by playing centers according to physical abilities and its effect on mastrring some of the basic offensive planning skills of handball player - a field study on players of some of the states on the state handball association of setif - Louati , abdesselam; sdira , saad (sports creativity, 2025)
This study coverd topic ‘ Speciqlist selection by playing centers according to physical abilities and its effect on mastrring some of the basic offensive planning skills of handball player ’, field study on playrs of some of the state handball association of setif, this study ained to know the effect of selection according to physical abilities to master some basic offensive tactical skills in handball, this is based on the experimental approach, the research sanple consisted of a control group consisting of 9 players and a experimental group consisting of 9 players, the information was used to collect information testes and a not card in addition to a set of training unites, the researcher concluded that the selection according to physical capabilities had a some offensive planing skills of handball players